2019
DOI: 10.1021/acssynbio.9b00314
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Substrate Transport and Cofactor Regeneration Systems for Enhancing 2′-Fucosyllactose Synthesis in Bacillus subtilis

Abstract: Human milk oligosaccharides (HMOs) have been proven to be beneficial to infants’ intestinal health and immune systems. 2′-Fucosyllactose (2′-FL) is the most abundant and thoroughly studied HMO and has been approved to be an additive of infant formula. How to construct efficient and safe microbial cell factories for the production of 2′-FL attracts increasing attention. In this work, we engineered the Bacillus subtilis as an efficient 2′-FL producer by engineering the substrate transport and cofactor guanosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 31 publications
1
50
0
Order By: Relevance
“…Whereas the most common cell factory platform for 2′-FL production reported so far is Escherichia coli [ 12 14 , 16 , 17 ], attempts have been also made in a few other microorganisms including Bacillus subtilis and Saccharomyces cerevisiae (Table 1 ). The latter microorganisms do not cause the specific concerns of endotoxin carryover as occurs with engineered E. coli [ 18 21 ]. In addition to being in its generally recognized as safe (GRAS) status, S. cerevisiae also has advantages over bacteria in not being susceptible to phage infections during fermentation as well as its rich intracellular pool of GDP-mannose, which make it a preferred production platform for 2′-FL [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the most common cell factory platform for 2′-FL production reported so far is Escherichia coli [ 12 14 , 16 , 17 ], attempts have been also made in a few other microorganisms including Bacillus subtilis and Saccharomyces cerevisiae (Table 1 ). The latter microorganisms do not cause the specific concerns of endotoxin carryover as occurs with engineered E. coli [ 18 21 ]. In addition to being in its generally recognized as safe (GRAS) status, S. cerevisiae also has advantages over bacteria in not being susceptible to phage infections during fermentation as well as its rich intracellular pool of GDP-mannose, which make it a preferred production platform for 2′-FL [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 A). To accomplish 2′-FL biosynthesis, α-1, 2-FT from H. pylori (FutC) which has been shown to be one of the most efficient α-1, 2-FTs in catalyzing the fucosyl transfer to lactose, was further overexpressed in FL03 under the gal1 promoter [ 12 , 16 , 18 ]. When the resulting FL04 strain was cultured in YP medium containing 2 g/L lactose for 72 h, the extracellular 2′-FL reached 1.18 g/L and the total 2′-FL measured after cell lysis was 1.41 g/L (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, to generate 2 ′ -FL from lactose and GDP-L-fucose present, a highly active α-1,2-FT sufficient in the cytoplasm is always necessary to facilitate the fucosylation reaction. Previous studies have identified a variety of various FT candidates, some of which, such as the futC gene from Helicobacter pylori (H. pylori) or wcfB gene from B. fragilis for an α-1,2-FT, provided the clear opportunities for efficient 2 ′ -FL synthesis in vivo (Chin et al, 2017;Huang et al, 2017;Deng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The de novo pathway later established in Y. lipolytica increased the 2′-FL titer from 15 to 24 g/L as compared with S. cerevisiae [47,48]. The substrates' import and the cofactor supply were improved in engineered Bacillus subtilis, and 5.01 g/L 2′-FL was obtained through introducing the salvage pathway and FucT2 from H. pylori [49,50].…”
Section: The Microbial Production Of 2′-fl and 3-flmentioning
confidence: 99%
“…[61][62][63]. Among these permeases, LacY and LAC12 have been overexpressed in FLs production strains and proved to be effective for improving the intracellular lactose supply [38,48,50]. By overexpressing the homologous lactose permease (LacY) and eliminating the β-galactosidase (LacZ), the engineered E. coli can consume almost all of the lactose during fermentation [44,51].…”
Section: The Microbial Production Of Lnnt and Lntmentioning
confidence: 99%